Green Brand Positioning and Attitude towards Green Brands: Mediating Role of Green Brand Knowledge among Green Consumers in the Kathmandu Valley (Quest Journal of Management and Social Sciences, 2023)
Background- The issue of sustainability has attracted global brands to take initiatives in green concerns. Following the footsteps of global brands, Nepali brands have designed their products to address such green concerns. As a result, green consumers' behaviors have gained the attention of different streams of researchers and practitioners.Purpose- The purpose of this paper is to examine the mediating role of Green Brand Knowledge (GBK) on Green Brand Positioning (GBP) and Attitude towards Green Brands (ATGB).Research Methodology- This paper adopted a quantitative approach to achieve the research objective. A cross-sectional survey research design and purposive sampling technique were employed to collect data from 201 green-aware customers of the Kathmandu Valley. The process macro was applied to test the mediated hypotheses.Results- The result revealed that GBP significantly influences GBK and ATGB, and GBK partially mediates the relationship between GBP and ATGB. Conclusion- This paper concluded that the GBP and GBK of customers could change the ATGB. Since ATGB is a significant variable, Nepali green brands could invest in a promotional campaign, as a result, GBK and GBP could change the positive attitude toward green brands.  Implications: This paper could provide two significant implications. First, it can help to enrich the existing body of literature on green branding by drawing from signaling theory (ST) and the theory of planned behavior (TPB). Second, this paper could help managers and marketers to design GBP strategy as it is regarded as a critical aspect of green brands. Originality: This paper is among the earliest work to explain green attitude by applying the ST and TPB in the Nepali context.